The perception of tourist towards security of Sabah Tourism / Norfatin Arifah Abd Wahab and Prizelea Mison - Abd Wahab, Norfatin Arifah; Mison, Prizelea (2014)
This research is being conducted in order to know about the perceptions of the tourists towards the security of Sabah Tourism. This research being conducted based on the cases of kidnapping and the intrusion that happen in Sabah that include the tourists. Basically, security is one of the crucial elements for the tourists in choosing the tourist destinations and the cases that happen in one place can give a negative perception towards the security level of that place. In addition, the security is important because it has relations with the economics of the country where the tourists are the main reasons of the increasing of the revenue of one country. From that, we come out with two main objectives based on this research study, which are firstly is to know the overall perception of the tourists towards the security of Sabah Tourism and secondly is to know the differences in perceptions among different tourist groups. The methods that being done in order to complete this research study are the research design is based on the case study analysis and theoretical framework. In order to get the analysis of the first objectives, we use the overall perception of the tourists by using the descriptive analysis where the second objectives, we use the Mann Whitney Test in order to know the difference in perception between the two groups of tourists. For the findings, we can see from the analysis that the majority of the tourists said that Sabah is a safe place and the mean perception is 3.00 and it show the moderate perception level of the tourists. While the second objective, the findings showed that it has significant differences in the perception level between the two groups where the value is 0.048. There are 102 respondents involved in this research study in order to know their perception level towards the safety of Sabah Tourism and the research being conducted at Jesselton Point, Universiti Teknologi Mara (UiTM) Kota Kinabalu and Universiti Malaysia Sabah (UMS) in order to answer our questionnaire.